Long Non-coding RNAs: Pivotal Epigenetic Regulators in Diabetic Retinopathy - Song, Zhaoxia; He, Chang; Wen, Jianping; Yang, Jianli; Chen, Peng (Current Genomics, 2022)
Diabetic retinopathy (DR) is a severe complication of diabetes; however, its mechanism is not fully understood. Evidence has recently revealed that long non-coding RNAs (lncRNAs) are abnormally expressed in DR, and lncRNAs may function as pivotal regulators. LncRNAs are able to modulate gene expression at the epigenetic level by acting as scaffolds of histone modification complexes and sponges of binding with microRNAs (miRNAs). LncRNAs are believed to be important epigenetic regulators, which may become beneficial in the diagnosis and therapy of DR. However, the mechanisms of lncRNAs in DR are still unclear. In this review, we summarize the possible functions and mechanisms of lncRNAs in epigenetic regulation to target genes in the progression of DR.
Keywords: epigenetics